2020
DOI: 10.1007/s00415-020-10237-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurological updates: neurological complications of CAR-T therapy

Abstract: Chimeric antigen receptor (CAR)-expressing T cells now offer an effective treatment option for people with previously refractory B cell malignancies and are under development for a wide range of other tumours. However, neurological toxicity is a common complication of CAR-T cell therapy, seen in over 50% of recipients in some cohorts. Since 2018, the term immune effector cell-associated neurotoxicity syndrome (ICANS) has been used to describe and grade neurotoxicity seen after CAR-T cells and other similar the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 55 publications
(203 reference statements)
2
21
0
Order By: Relevance
“…In all cases, paligraphia was followed by a rapid neurological deterioration with frontal predominant encephalopathy that required transfer to ICU for three patients. In previous studies, neurotoxicity was observed with a mean onset of 5 days after infusion, even though it developed within 24 h since reinfusion in a subgroup of patients [ 7 , 11 ], as we observed in two cases, requiring early management. Despite the use of specific aggressive treatment, one of our cases died from CAR T-cell therapy-related toxicity, while another one because of CAR T-cell therapy failure (disease progression).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In all cases, paligraphia was followed by a rapid neurological deterioration with frontal predominant encephalopathy that required transfer to ICU for three patients. In previous studies, neurotoxicity was observed with a mean onset of 5 days after infusion, even though it developed within 24 h since reinfusion in a subgroup of patients [ 7 , 11 ], as we observed in two cases, requiring early management. Despite the use of specific aggressive treatment, one of our cases died from CAR T-cell therapy-related toxicity, while another one because of CAR T-cell therapy failure (disease progression).…”
Section: Discussionsupporting
confidence: 55%
“…Clinical manifestations of ICANS are heterogeneous and may have a progressive or fluctuating course, ranging from mild cognitive slowing, headache and tremor, to language disorders, seizure, motor deficits and encephalopathy, potentially leading to akinetic mutism and death [ 2 , 3 ]. Steroids are currently the first-line therapy for ICANS, despite potential interference with CAR T-cell anti-tumour action [ 2 , 5 , 7 , 8 ]. Hence, it is paramount to identify early clinical and instrumental findings of neurotoxicity to detect early stages of ICANS, define the prognosis and guide the appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that COVID-19 patients could develop a form of cytokine-mediated neuroinflammatory encephalopathy, the immune effector cellassociated neurotoxicity syndrome (ICANS), due to the massive cytokine storm induced by COVID-19 systemic infection [13]. ICANS is a neuropsychiatric syndrome that may include frontal-type changes, such as confusion, short-term memory impairment, expressive deficits, and behavior disturbances including impulsivity, emotional lability, abulia, or akinetic mutism as clinical phenotype [13,21,22].…”
Section: Pathophysiological Theoriesmentioning
confidence: 99%
“…These include non-ubiquitous expression of the target antigen, physical barriers such as the blood–brain barrier (BBB) and extracellular matrix, immunosuppressive cells and cytokines, which are all present within a hostile, often hypoxic tumour microenvironment [ 34 ]. These obstacles are compounded by antigen loss [ 69 ] and serious adverse events observed in CAR T clinical trials, such as immune effector cell-associated neurotoxicity syndrome (ICANS) [ 70 ] and cytokine release syndrome (CRS) [ 71 ] in a brain encapsulated in an unyielding, bony cranium.…”
Section: Past Experiences and Thinking Forward With Car T Cell Therapymentioning
confidence: 99%